THE OPTIMALIZATION OF WORSHIP LEARNING DEVELOPMENT DURING PANDEMIC PERIOD AT RA AL ROSYID KENDAL NGUMPAKDALEM DANDER BOJONEGORO - Ulfa Ulfa (LPPM STAI Muhammadiyah Probolinggo, 2021)
There are many teenagers who don't pray, fast, even can't read Al-Qur'an. One of the reasons is the lack of religious education since at the early childhood. The important thing that that need to be instilled in early childhood is religious education which one of them is the introduction and habituation of worship. Because, what is introduced and accustomed from the early age, it will become the basis of religion until adulthood. RA Al Rosyid Ngumpakdalem Dander Bojonegoro is an educational institution that has its own characteristics that enrich research findings. The purpose of this study is to describe the introduction of worship learning in early childhood which includes the learning process and materials for the introduction of worship in early childhood. This study uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. The data collected from these techniques were analyzed using the Miles and Huberman interactive analysis model which divided the analytical activities into data collection, data display, data reduction and conclusion drawing. Based on the results of data analysis, findings can be obtained that the process of introducing worship at early childhood children is carried out. Based on the results of the researcher's analysis, there are several things in optimizing the development of learning, which are: The development of early childhood worship learning at RA Al Rosyid Ngumpakdalem Dander Bojonegoro develops according to expectations with the indicator achievement of religious and moral values for early childhood children. Religious education methods that applied at RA Al Rosyid Ngumpakdalem Dander Bojonegoro during COVID-19 pandemic period learning was more focused on the use of exemplary methods, habituation, advice, storytelling, and memorization methods